Investment Bank Power and Neoliberal Regulation: From the Volcker Shock to the Volcker Rule - Sandy Brian Hager (Neoliberalism in Crisis, 2012)
The power of investment banks has played a pivotal role in the monopoly capital school's analyses of US capitalist development. However this paper suggests that monopoly capital's explanation of the changing nature of this power is severely limited. These limitations can be traced to the school's logically circular and empirically inoperable theory of capital accumulation. The paper goes on to offer an alternative theoretical-empirical account of the power of investment banks since the early 1980s. Based on the notion of capital as power, the research suggests, contrary to the monopoly capital account, that investment banks have experienced a rapid resurgence in their power over this period. This resurgence must be understood with reference to the unique ways that investment banks have maneuvered within neoliberal regulation.
Keywords: 330; investment banking; monopoly; capital; power